2016
DOI: 10.1186/s12014-016-9125-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased sialylation of site specific O-glycoforms of hemopexin in liver disease

Abstract: BackgroundNon-invasive monitoring of liver disease remains an important health issue. Liver secreted glycoproteins reflect pathophysiological states of the organ and represent a rational target for serologic monitoring. In this study, we describe sialylated O-glycoforms of liver-secreted hemopexin (HPX) and quantify them as a ratio of disialylated to monosialylated form (S-HPX).MethodsWe measured S-HPX in serum of participants of the HALT-C trial using a LC–MS/MS-MRM assay.ResultsRepeated measurements of S-HPX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…GluC, PNGase F, neuraminidase and beta galactosidase digests of tryptic peptides were carried out as described previously (11,12) with heat inactivation (99 °C for 10 min) prior to the addition of any enzyme.…”
Section: Glycopeptide Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…GluC, PNGase F, neuraminidase and beta galactosidase digests of tryptic peptides were carried out as described previously (11,12) with heat inactivation (99 °C for 10 min) prior to the addition of any enzyme.…”
Section: Glycopeptide Preparationmentioning
confidence: 99%
“…We have used the m/z 657 ion to assign sialylation of the core-2 monosialylated structures. We used an optimized procedure based on a hemopexin glycopeptide standard, which we described previously (12), and we determined CCS of the fragment 657 ( Figure 6) observed by fragmentation of the glycopeptide with sialyl-T antigen with linkage (α2-3) (CCS 234.9) and by fragmentation of an Nglycopeptide with sialyl-LacNAc with (α2-6) linkage (CCS 232.8) (data not shown). This is in agreement with the previously published results on the linkages of the sialylated glycans (6,8).…”
Section: Structural Analysis Of the O-glycopeptides Using Cimsmentioning
confidence: 99%
“…Serum samples of 15 disease-free controls were collected at Georgetown University Medical Center under protocols approved by the Institutional Review Board. De-identified serum samples of 30 patients with various degree of liver fibrosis were obtained from the hepatitis C antiviral long-term treatment against cirrhosis trial (HALT-C), as described in our recent study [35]. The HALT-C trial, a prospective randomized controlled trial of 1050 patients, evaluated effect of long-term low-dose peginterferon alpha-2a (IFN) in participants that failed initial anti-HCV therapy with interferon [37,38].…”
Section: Methodsmentioning
confidence: 99%
“…Liver disease status of the HALT-C participants was classified into fibrosis (Ishak score 3–4) or cirrhosis (Ishak score 5–6) based on biopsy-evaluation. All the participants selected for this study were from the control arm of the HALTC trial that did not receive IFN treatment [35]. Method optimization was carried out on a sample pooled from the 45 serum samples of all participants (equal volume of each) and the pooled sample served as a quality control (QC) that was analyzed in parallel with the analyses of the 45 study samples.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we developed a mLC-MS/MS-PRM assay for the quantification of site-specific mucin-type O-glycoforms of hemopexin, which we previously reported as a promising candidate biomarker for the serologic monitoring of liver fibrosis [ 11 , 12 ]. We have shown that the sialylated O-glycoforms of hemopexin (HPX) in serum of patients are associated with advancing fibrosis in hepatitis C-associated liver disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%